2002
DOI: 10.1271/bbb.66.2683
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Theanine of Binding of [3H]AMPA, [3H]Kainate, and [3H]MDL 105,519 to Glutamate Receptors

Abstract: In an investigation of the mechanisms of the neuroprotective eŠects of theanine (g-glutamylethylamide) in brain ischemia, inhibition by theanine of the binding of [ 3 H](RS )-a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA), [ 3 H]kainate, and [ 3 H]( E )-3-(2-phenyl-2-carboxyethenyl)-4,6-dichloro-1-H-indole-2-carboxylic acid (MDL 105,519) to glutamate receptors was studied in terms of its possible inhibiting eŠects on the three receptor subtypes (AMPA, kainate, and NMDA glycine), with rat cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 17 publications
(13 reference statements)
1
56
0
Order By: Relevance
“…Moreover, because theanine did not change the glutamate level in the perfusate (Fig. 3a), theanine itself might have acted on AMPA/kainate receptors directly (Kakuda et al 2002a). …”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, because theanine did not change the glutamate level in the perfusate (Fig. 3a), theanine itself might have acted on AMPA/kainate receptors directly (Kakuda et al 2002a). …”
Section: Discussionmentioning
confidence: 97%
“…(Moghaddam et al 1990;Yadid et al 1993;Koga and Momiyama 2000). Because the chemical structure of theanine is similar to glutamic acid, some studies of theanine examined its relationship to glutamic acid function and metabolism (Sugiyama et al 2003;Kakuda et al 2002a;Tsuge et al 2003;Oda et al 1980); however, the glutamate receptor antagonist MK-801 did not affect the increase of dopamine concentration by theanine injection in the rat striatum (Yokogoshi et al 1998a). This result suggested that theanine did not affect glutamate neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations